Perlindungan Hukum terhadap Hak Penguasaan Tanah Ornamen yang Dialihkan oleh Pihak Lain di Kabupaten Gowa - Megawati Putri Ayustini; Abrar Saleng; Ilham Arisaputra (LPPM Universitas Ekasakti Padang, 2023)
This study discusses the legal protection of ornamental land tenure rights transferred by other parties in Gowa Regency. The type of research in this research is normative juridical which means the approach is carried out by examining the approaches of theories, concepts, reviewing the laws and regulations concerned with this research or the statutory approach. The type of approach used in this research is the statute approach. The statutory approach is an approach carried out by examining all laws and regulations that are related to the problems (legal issues) that are being faced. The results of this study are: 1) The transfer of rights to ornamental land in Gowa Regency can only be carried out by the Government as the holder of the land rights. Based on Perbup Number 13 of 2018, the Government, in this case the Regent, has the authority to issue permits for land leases. Instead, tenants are required to pay rent fees in the form of levies every year. The lessee is expressly prohibited from transferring the land to another party, whether a person or a business entity, without the permission of the government; 2) Legal protection for holders of lease permits for ornamental land is provided by the Government in the form of an Approval Letter. Tenure rights end at the end of the period the agreement is given. If the lessee transfers the land to another party (third party), then without the government's knowledge, the Letter of Approval must be null and void. Because the subject of the letter has changed